The Urgency of First Language Acquisition in Three-Year-Olds - Erra Malinda; Sholihatul Hamidah Daulay (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Children learn to speak their native language through a process known as language acquisition. Instead of being subjected to the same conditioning as adults, children are born with the innate ability to pick up a new language as part of their natural development. The aim of this research is to understand the challenges involved in teaching children their first language and to gain insight into the process by which infants acquire this language through the development of its syntactic, semantic, and pragmatic components. Qualitative methods were used in this study to examine the first language acquisition of children aged 3 years. The participants in this study were a 3-year-old child and her biological mother. Interviews and observations of children and mothers were conducted to obtain the necessary data. The result is that children aged 3 years are found to have problems in syntactical, phonological, and pragmatic